The major risk factors for road traffic injuries (One Health & Risk Management, 2021)
Introduction. Injuries caused by road crashes are major public health problem because they are the cause of 98.8% of the total number of transport accidents. Annually, as a result of the global traffic, more than 1.3 million people die and 20-50 million are with no injuries and it is the main cause of mortality of young people aged 15-29. Road injuries ranks 8th after the leading causes of death and is forecast to rank fifth by 2030. This public health problem is widespread thanks to the social and economic sequelae that can influence the development and stability of countries. The negative social and economic impact for the people affected, for their families and for the country as a whole is very high. Children, pedestrians, cyclists and the elderly remain among those most at risk of road accidents.Material and methods. A specialized search was conducted within the main international databases as: PubMed/MEDLINE, Google Scholar and Research Gate. The search was done by applying Boolean operators: road trauma AND accident, road trauma AND risk factors, “road trauma” AND “risk factors”, (trauma OR risk factor) car accident. Considering the significant amount of information published on the topic, the search was limited to a period of 10 years (2010-2020). The inclusion criteria were the following: studies related to motor vehicle crashes and risk factors, original research, observational studies and systematic reviews, full-text articles, book chapters, papers presented at conferences written in English and published in open access. Data and references were extracted and systematized into results tables, including: author/citation, study design, assessments/data, limitations, key facts. Reported outcomes were compiled in narrative form.Results. A flow diagram was created based on the inclusion criteria in this review in regard to the major risk factors and their contribution in motor vehicle injuries. From the total of 4535 results, 87 studies were included in the evaluation.  Road injuries have been studied by many researchers and scientists both in the country and abroad. According to the evaluated data, the authors of the studies used different methods and obtained obvious data about road traumas and major risk factors. Among the main causes of unintentional motor vehicle injuries where underlined: excessive speed, alcohol consumption while driving, psychological trauma, drugs, unsupervised children. During the last years there is an increasing tendency of road injuries among children, and most of the road accidents with their involvement occur in May-September, between 11.00 and 18.00. Statistics confirm that 81% of all cases of road trauma in children are the result of their non-compliance with traffic rules. Among the most effective actions in reducing road injuries, being mentioned: activities aimed at sensitizing the general public in a safer traffic, communicating road traffic risks, raising driver’s awareness, educating pedestrians for correct behavior on the streets; seat belt coupling; compliance with road traffic regulations.Conclusions. There are many factors which contributes to road crashes and related injuries, but they can be prevented. The obtained ones further motivate us the need to study this topic in more depth, on separate age groups and to propose specific prevention measures for each actor involved in.